Integrating life cycle assessment into green infrastructure: a systematic review and meta-analysis of urban sustainability strategies - Negin Bani Khalifi; Dafni Despoina Avgoustaki; Thomas Bartzanas (Frontiers in Sustainable Cities)
Green infrastructure (GI) is increasingly vital for cities addressing environmental challenges, climate change, and sustainability through nature-based solutions. However, the inconsistent use of life cycle assessment (LCA) methods—including variations in impact categories, data collection methods, system boundaries, and functional units—hinders effective policymaking and comparison among projects. This study conducted a systematic review and semi-quantitative meta-analysis, following PRISMA guidelines. Out of 334 publications (2014–2024) identified from Web of Science, Science Direct, and Google Scholar, 40 studies met the inclusion criteria. Analysis included critical sustainability indicators: carbon emissions, water footprint, energy use, land-use changes, and air pollution. Traditional LCA was most commonly applied, yet integration with economic (life cycle costing, LCC) and social dimensions (social LCA, S-LCA) remained limited. Meta-analysis indicated a slight positive correlation between standard LCA and water footprint (0.27) but a negative correlation with energy consumption (−0.18), suggesting trade-offs between water management and energy efficiency. Economic assessments (LCC) were moderately linked to land-use changes (0.15), reflecting economic considerations in GI projects. Social assessments (S-LCA) correlated positively with air pollution (0.20), highlighting potential conflicts between social and environmental objectives. Although GI significantly contributes to urban sustainability, the lack of standardized LCA methods limits comparative analyses and practical policy development. Standardizing methodologies, unifying impact assessments, integrating environmental, economic, and social evaluations, and developing financial incentives and advanced technological tools like artificial intelligence are critical steps forward. Future research should prioritize refining LCA accuracy, comprehensive lifecycle cost–benefit integration, and multi-dimensional sustainability analyses to better inform urban resilience policies.